2017
DOI: 10.1177/2053168017712821
|View full text |Cite
|
Sign up to set email alerts
|

Understanding state preferences with text as data: Introducing the UN General Debate corpus

Abstract: Every year at the United Nations, member states deliver statements during the General Debate discussing major issues in world politics. These speeches provide invaluable information on governments' perspectives and preferences on a wide range of issues, but have largely been overlooked in the study of international politics. This paper introduces a new dataset consisting of over 7,300 country statements from 1970-2014. We demonstrate how the UN General Debate Corpus (UNGDC) can be used to derive country positi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
98
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 124 publications
(100 citation statements)
references
References 22 publications
0
98
0
2
Order By: Relevance
“…Sources of transcript data reported in the included studies are shown in Table 1. Similarly, for speeches not originally in English, Baturo, Dasandi & Mikhaylov (2017) use official translations from the other official languages of the UN (Arabic, Chinese, French, Russian, and Spanish). By far the most prominent language is English, analysed in 55 studies.…”
Section: Parliaments and Legislaturesmentioning
confidence: 99%
“…Sources of transcript data reported in the included studies are shown in Table 1. Similarly, for speeches not originally in English, Baturo, Dasandi & Mikhaylov (2017) use official translations from the other official languages of the UN (Arabic, Chinese, French, Russian, and Spanish). By far the most prominent language is English, analysed in 55 studies.…”
Section: Parliaments and Legislaturesmentioning
confidence: 99%
“…These data are available online at: Harvard Dataverse 1902.1/12379. In addition, we utilize the record of annual speeches delivered by country representatives -often heads of state -during the annual UN General Debate [42]. These speeches are stored as plain text files with associated metadata and are available online at: Harvard Dataverse doi.org/10.7910/DVN/0TJX8Y.…”
Section: Datamentioning
confidence: 99%
“…We draw on the newly released UN General Debate Corpus [42] which contains every country statement in the UN General Debate between 1970 and 2017. The General Debate (GD) takes place every September at the start of each new session of the UN General Assembly (UNGA).…”
Section: Supplementary Information the Un General Debate Corpusmentioning
confidence: 99%
See 1 more Smart Citation
“…We use a new dataset of GD statements from 1970 to 2016, the UN General Debate Corpus (UNGDC), to examine the international development agenda in the UN [4]. 1 Our application of NLP to these statements focuses in particular on structural topic models (STMs) [5].…”
Section: Introductionmentioning
confidence: 99%